2012
DOI: 10.1039/c2mb05400k
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profile and biological activity of caprine, bovine and human milk fat globules

Abstract: Upon combining bidimensional electrophoresis with monodimensional separation, a more comprehensive analysis of the milk fat globule membrane has been obtained. The proteomic profile of caprine milk fat globules revealed the presence of butyrophilin, lactadherin and perilipin as the major proteins, they were also associated to bovine and human milk fat globule membranes. Xanthine dehydrogenase/oxidase has been detected only in monodimensional gels. Biological activity of milk fat globules has been evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…These proteins are thus specific to EV derived from milk (and have not been identified in other EV preparations). Moreover, OLAH could potentially be used to differentiate between milk-derived EV and MFG, as some studies performed on MFG have reported the presence of PTHLH, whereas OLAH has never been detected in this milk component (31)(32)(33)37). Both OLAH and PTHLH have been detected in whey (36,45), which contains EV but not MFG, further supporting the idea that milk-derived EV express both OLAH and PTHLH.…”
Section: Discussionsupporting
confidence: 53%
“…These proteins are thus specific to EV derived from milk (and have not been identified in other EV preparations). Moreover, OLAH could potentially be used to differentiate between milk-derived EV and MFG, as some studies performed on MFG have reported the presence of PTHLH, whereas OLAH has never been detected in this milk component (31)(32)(33)37). Both OLAH and PTHLH have been detected in whey (36,45), which contains EV but not MFG, further supporting the idea that milk-derived EV express both OLAH and PTHLH.…”
Section: Discussionsupporting
confidence: 53%
“…A primary function of PLIN proteins is the regulation of lipolysis by controlling lipase access to the TAG core of CLD (33, 3739). Perilipin 2, which appears to be the primary PLIN family member expressed by mammary epithelial cells (16, 40–42), is an abundant protein on lipid droplets isolated from the milk of rodents, cattle, and humans (16, 43, 44). PLIN2 transcripts are selectively enriched in mammary epithelial cells in the mouse mammary gland relative to other cell types (42), and their levels undergo about a 30-fold increase during mammary gland differentiation (42).…”
Section: Mechanisms Of Milk Lipid Productionmentioning
confidence: 99%
“…; Spertino et al . ). To our knowledge, this is the first use of proteomics technology to discern changes in secretory mechanisms following knockout of a specific mediator of apocrine secretion.…”
Section: Introductionmentioning
confidence: 97%